Frontline. The spill [videorecording (DVD)] - Lyman, Will, 1948-; Lustgarten, Abrahm; Smith, Martin (Martin E.); Smith, Martin (Martin E.) (PBS Distribution, 2011)
Martin Smith and Abraham Lustgarten explore the corporate history of BP before the 2010 Deepwater Horizon explosion in the Gulf of Mexico. This investigation reveals a history of safety and environmental violations.